Immunotherapeutic Strategies in Cancer and Atherosclerosis—Two Sides of the Same Coin - Nettersheim, Felix Sebastian; Picard, Felix Simon Ruben; Hoyer, Friedrich Felix; Winkels, Holger (Frontiers in Cardiovascular Medicine, 2022)
The development and clinical approval of immunotherapies has revolutionized cancer therapy. Although the role of adaptive immunity in atherogenesis is now well-established and several immunomodulatory strategies have proven beneficial in preclinical studies, anti-atherosclerotic immunotherapies available for clinical application are not available. Considering that adaptive immune responses are critically involved in both carcinogenesis and atherogenesis, immunotherapeutic approaches for the treatment of cancer and atherosclerosis may exert undesirable but also desirable side effects on the other condition, respectively. For example, the high antineoplastic efficacy of immune checkpoint inhibitors, which enhance effector immune responses against tumor cells by blocking co-inhibitory molecules, was recently shown to be constrained by substantial proatherogenic properties. In this review, we outline the specific role of immune responses in the development of cancer and atherosclerosis. Furthermore, we delineate how current cancer immunotherapies affect atherogenesis and discuss whether anti-atherosclerotic immunotherapies may similarly have an impact on carcinogenesis.